KEWENANGAN PERUSAHAAN DAERAH AIR MINUM ATAS PENGELOLAAN AIR BERSIH DI KABUPATEN BADUNG - Banda Prawira, I Made; Sudiarta, I Ketut; Dahana, Cokorda Dalem (Kertha Negara : Journal Ilmu Hukum, 2014)
Regional Water Company (PDAM) of Badung Regency has the authority and responsibility for water resource management, including regulating, deciding and providing licenses for provision of supply, use and cultivating of water resources. The authority of Regional Water Company (PDAM) of Badung in providing general service creates an opportunity which possibly causes disputes to occur between Regional Water Company (PDAM) as the party having authority to water resource and community as the customers. In relation to such matter, this paper discusses two problems: 1. The authority of Regional Water Company of Badung Regency for drinking water management in Badung Regency; 2. The legal liability of Regional Water Company (PDAM) of Badung Regency, in the event of disputes arise with service users of Regional Water Company. The method applied is normative research methods. The conclusions obtained are: 1. The Regional Water Company (PDAM) of Badung Regency in implementing its authority on water supply management requires agreement or power of attorney from the chief of the region through supervising board especially in determining rate; 2. In the event of a dispute arises, the settlement is prioritized through non litigation procedures, litigation action through district court.
Keywords: Authority, PDAM (Regional Water Company), Drinking Water Management, Badung Regency